Stwierdzenie stanu wolnego wiernych Kościoła Ewangelicko‑Augsburskiego w Polsce przed zawarciem małżeństwa w Kościele katolickim - Nowicka, Urszula (Ius Matrimoniale, 2016)
Along with the Catholic Church study, a marriage contracted between the baptized in a valid way is a sacrament and for his reason neither human power nor any cause can dissolve it, only the death. While the practice of the Lutheran Church in Poland provides a different perception of the same fundamental rules. Lutheran Church accepts divorce granted by secular law and allows of successive marriage by the faithful in Church. The purpose of this article is analysis of the situation when the Lutheran faithful intends to contract a marriage with a Catholic party and in the Catholic Church.